A Cross-Cultural Comparison of Tourists’ Perceptions of Hotel Lobbies - Köseoğlu, Emine; Erinsel Önder, Deniz; Bilen, Ömer (International Journal of Architectural Research, 2012)
This study examines cultural differences in the perception of hotel lobbies. It aims to determine the differences/similarities within spatial preferences in hotel lobbies by focusing on three aspects of space: physical appearance, configuration, and usage and privacy arrangements. To measure the differences, a survey is conducted in Sultanahmet, Istanbul with tourists within two focus groups from Asian and European countries (n= 30 each). They are asked to rate their agreement with each statement about the spatial features on a 5-point Likert scale. As a result, both differences and similarities in the perception of the tourists from different cultures are found. It can be noted that there are statistically significant differences between the two groups in terms of configurational features and usage and privacy arrangement of lobbies. The results provide designers some data to create a space for similar user profiles.
Keywords: Cultural Differences; Spatial Perception; Touris Behaviour; User Preferences